Medieval and renaissance music : a performer's guide - McGee, Timothy J. (Timothy James), 1936- (Book collections on Project MUSE., 1988)
At the time of publication, this book was the first to address the problem of how to perform medieval and Renaissance music. It is intended for both the amateur performing musician and the serious student.